Rat liver arginase system under acetaminophen-induced toxic injury and protein deprivation - Kopylchuk, Н. P.; Nykolaichuk, I. M.; Zhuretska, O. M. (Ukr. Biochem. J., 2017)
Arginase activity and L-arginine content in both cytosolic and mitochondrial fractions of rat liver cells under the conditions of toxic injury on the background of protein deprivation was studied. The most significant reduction of arginase activity in liver cells and depletion of L-arginine pool was found in rats with toxic acetaminophen-induced liver injury maintained on the ration balanced by all nutrients as well as in protein deficiency rats. It was concluded that reduction of the arginase activity in the cytosolic fraction of rat liver cells, combined with simultaneous decrease of L-arginine content, may be considered as one of the mechanisms of ornithine cycle disturbance. The decline of activity of mitochondrial isoform of arginase II, for certain, is related with activation of NO-synthase system.
Keywords: Acetaminophen; Alimentary deprivation of protein; Arginase; L-arginine; Toxic injury